Evaluasi dan Pengembangan Usaha Pesantren Teknologi Riau Berbasis Manajemen, Digitalisasi, dan Nilai Islam - Zahwatul Nadia; Arianwen Sa’adi; Akhmad Turmudzi; Nurnaningsih (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2026)
This study aims to evaluate business implementation at Pesantren Teknologi Riau, identify management constraints, analyze factors affecting business development, and formulate effective, sustainable strategies based on Islamic values. This study used a qualitative approach with a case study design. Data were obtained through in-depth interviews, participant observation, and documentation involving pesantren leaders, business managers, and students participating in business activities. Data were analyzed through the stages of data reduction, data presentation, conclusion drawing, and thematic analysis, supported by triangulation to strengthen the validity of the findings. The findings show that business implementation has run well, particularly through student involvement as a medium for entrepreneurship learning. However, business management remains constrained by unsystematic planning, simple financial recording, limited marketing, weak product innovation, and suboptimal use of digital technology. The main factors influencing business development include human resource quality, business management systems, marketing strategies, and product innovation. Thus, stronger management, digital marketing, human resource training, and integration of Islamic values are needed to support sustainable pesantren business development. These findings contribute to the development of an adaptive, educational, and sharia-based business model for pesantren economic independence in the current digital era.